Health outcomes after pregnancy in elite athletes: A systematic review and meta-analysis - Kimber, M. L.; Meyer, S.; McHugh, T.-L.; Thornton, J.; Khurana, R.; Sivak, A.; Davenport, M. H. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to evaluate postpartum maternal health and training outcomes of females who were competing or training as elite athletes before or during pregnancy. Methods: Online databases were searched up to August 26, 2020. Studies of any design and language were eligible if they contained information on the relevant population (postpartum athletes [any period after pregnancy]), exposure (engaged in the highest level of sport immediately before or during pregnancy), comparators (sedentary/active controls), and outcomes: maternal (breastfeeding initiation and duration, postpartum weight retention or loss, bone mineral density, low back or pelvic girdle pain, incontinence [prevalence or severity of stress, urge or mixed urinary incontinence, fecal incontinence], injury, anemia, diastasis recti, breast pain, depression, anxiety) and training (<6 wk time to resume activity, training volume or intensity, performance level). Results: Eleven studies (n = 482 females, including 372 elite athletes) were included. We identified "very low" certainty evidence demonstrating a higher rate of return to sport before 6 wk postpartum among elite athletes compared with nonelite athletes (n = 145, odds ratio = 6.93, 95% confidence interval = 2.73-17.63, I2 = 11). "Very low" certainty evidence from three studies (n = 179) indicated 14 elite athletes obtained injuries postpartum (7 stress fractures, 9 "running injuries"). "Very low" certainty evidence from five studies (n = 262) reported that 101 (40.5%) elite athletes experienced improved performance postpartum. Conclusion: Compared with controls, "very low" quality evidence suggests that elite athletes return to physical activity early in the postpartum period and may have an increased risk of injury. Additional high-quality evidence is needed to safely guide return to sport of elite athletes in the postpartum period.